A homozygous mutation in CMAS causes autosomal recessive intellectual disability in a Kazakh family. (8th September 2019) - Qu, Ronggui; Sang, Qing; Wang, Xueqian; Xu, Yao; Chen, Biaobang; Mu, Jian; Zhang, Zhihua; Jin, Li; He, Lin; Wang, Lei
Abstract: Intellectual disability (ID) describes a wide range of serious human diseases caused by defects in central nervous system development and function. Some mutant genes have been found to be associated with these diseases, but not all cases can be explained, thus suggesting that other disease‐causing genes have not yet been discovered. Sialic acid is involved in a number of key biological processes, including embryo formation, nerve cell growth, and cancer cell metastasis, and very recently it has been suggested that N ‐acetylneuraminic acid synthase‐mediated synthesis of sialic acid is required for brain and skeletal development. CMP‐sialic acid synthetase (CMAS) is one of four enzymes involved in NeuNAc metabolism, as it catalyzes the formation of CMP‐NeuNAc. Before the present study, no links between mutations in CMAS and incidences of human ID had been reported. In the current study, we recruited a recessive nonsyndromic ID pedigree with consanguineous marriage in which all patients have typical clinical manifestations of ID. We identified the NM_018686.3:c.563G > A (p.Arg188His) substitution in CMAS as being responsible for the disease in this family. Conservation analysis, structural prediction, and enzyme activity experiments demonstrated that (p.Arg188His) influences protein dimerization and alters CMAS enzyme activity. Our results offer a new orientation for future research and clinical diagnosis.